(untitled) (Innovative Technologica: Methodical Research Journal, 2021)
The development and application of energy-efficient, high-performance and high-quality pre-sowing tillage machines is a world leader. [1] “Today, the world spends 1.8 billion annually on sowing the seeds of agricultural crops. Given that the area is cultivated per hectare, the machines used in pre-sowing tillage should be energy-efficient, high-quality and productive. In this regard, it is important to improve the techniques used in pre-sowing tillage on a scientific basis. Targeted research is being carried out around the world to create resource-saving technologies for the preparation of fields for sowing of agricultural crops and new models of equipment, to develop scientific and technical bases for improving existing ones, to ensure resource efficiency in the work process. [2]